Dinâmica Geoambiental do Sistema Hídrico Maceió/Papicu - Maia, Edemir Barros (2010)
This research aims to analyse the geo-environmental features of the Maceió/ Papicu Hydrical System relating the dynamic in the natural landscape to the human aspects. The survey is based on the process of degradation from occupation considering the changes and their consequences to the environment. By means of the visual interpretation of the AUMEF 1978 air photographs, scale 1:8.000, they were delimited the geo-morphological units‟ surroundings and the hydrical resources in the system. The Quickbird 2003 and 2008 satellite images, informal interviews with riverine habitants, water collecting and analysis, and previously developed researches in the area were used to understand the present occupation. The studied place, which is situated in the Fortaleza city‟s East sea side, is composed by elements originated from the sea and dunes dynamics, whose their riverine and lacustrine hydrical system was neglected for a long time allowing the coast occupation by the tourist enterprises and irregular occupation in the protected areas, which was promoted by the real estate speculators and homeless people. Nowadays, the complex is totally urbanised and has a high populational density, satisfactory infrastructure and its artificial components make it an urban ecosystem. The lagoon and the rivers of the complex have been constantly affected by the intervention causing drastic impacts: in their cannals were built bridges, railroads, residences, condominia and apartments; streets, avenues and buildings delimited their edges; and landfills and sewages contribute to the water quality in the local hydrical resources. The water analysis proved that the area received a considerable pollutant load, specially fecal coliform bacteria, which deteriorated the water quality and its use for bathing and supplying. Consequently, the population established in the place is on risk of contamination and susceptible to the problems that occur in all the Maceió/ Papicu Hydrical System.